The Analysis of Humanism as Represented in The Animation Series “Astro Boy” - Phoebe Charis Homidan (Journal of Art, Film, Television, Animation, Games and Technology, 2023)
This journal will discuss the topic of humanism as a subject brought by the genre of science fiction—specifically in the animated series Astro Boy. The social and psychological commentary of the idea given that, if an intelligent life were not human, would you and others treat it the same way? It is depicted in Astro Boy through still and moving images to tell a story about people and humanity. It is expressed in a neat and concise way as to beunderstood by all audiences from every background. It’s the reason why the series is so popular worldwide, even to this day.